Seeking the needle in the haystack: Undetectability of mycorrhizal fungi outside of the plant rhizosphere associated with an endangered Australian orchid. (June 2018) - Egidi, Eleonora; May, Tom W.; Franks, Ashley E.
Abstract: Co-occurrence and abundance of suitable mycorrhizal fungi are expected to be important drivers for orchid seedling establishment and development, as well as mature plant distribution. However, limited information is available on the occurrence and spatial patterns of orchid mycorrhizal fungi in soil independent of the orchid host. In this study, we investigated the in situ distribution of Tulasnella spp. associated with the critically endangered Australian orchid Diuris fragrantissima. We tested and implemented a meta-barcoding approach (fungal ITS1 region) using three soil sources: orchid rhizosphere, orchid-associated bulk soil and bulk soil from the orchid native site. The quality-filtered data set revealed that the occurrence of Tulasnella spp. in situ is restricted to the orchid rhizosphere, suggesting that a limited number of potential recruitment micro-sites with suitable mycorrhizal taxa exists in the D. fragrantissima natural habitat. The meta-barcoding approach also revealed a distinctive fungal community associated with the orchid rhizosphere. Overall, Next Generation Sequencing technology has proven to be a suitable method for large-scale screening of mycorrhizal fungi in orchid-associated soil.